Huma Betang Sebagai Wadah Moderasi Beragama di Desa Nihan Kecamatan Nihan Hilir Kabupaten Barito Utara - Andreas, Billy (Dharma Duta, 2024)
This study aims to examine the role of Huma Betang as a medium of religious moderation in Nihan Village, Nihan Hilir Subdistrict, Barito Utara Regency. Huma Betang represents the Dayak community’s values of unity, tolerance, mutual cooperation, and respect for diversity. The research employed a qualitative approach through observation, in-depth interviews, and documentation study. The findings indicate that Huma Betang functions not only as a traditional communal house but also as a social and cultural space that fosters religious moderation through interfaith dialogue, customary deliberations, and collective activities across beliefs. Supporting factors include the roles of traditional leaders, religious leaders, and the preservation of local wisdom values. Nevertheless, challenges arise from modernization, which reduces younger generations’ understanding of the philosophical meaning of Huma Betang. This study concludes that Huma Betang plays a vital role as a model of local wisdom in strengthening religious moderation and promoting harmony in multicultural communities.